Reduction of humeroulnar congenital elbow luxation in 8 dogs by using the transarticular pin - Rahal, Sheila Canevese [UNESP]; De Biasi, F.; Vulcano, Luiz Carlos [UNESP]; Teixeira Neto, Francisco José [UNESP] (Canadian Vet Med Assoc, 2000)
The purpose of this study was to evaluate the clinical and radiographic outcome in 8 dogs of surgical reduction of congenital humeroulnar luxation by using the transarticular pin. Five cases were bilateral and 3 were unilateral, for a total of 13 elbows. The treatment was performed in animals between 45 and 150 days of age. Articular stabilization was achieved by using a transarticular pin driven from the caudal aspect of the olecranon into the body of the humerus or into the distal condyle and distal metaphysis of the humerus. The follow-up period was between 1 and 19 months. There were 5 postsurgical reluxations, 3 related to the insertion of the pin into the humeral condyle and 3 related to the insertion into the humeral body. These animals needed further surgery. Six animals showed near normal return to limb function and 2 had lameness. We conclude that the use of the transarticular pin is an effective and simple method for the treatment of humeroulnar congenital elbow luxation.